Stability of an Oldroydian tluid layer in a horizontal magnetic field - Bhatia, P.; Khan, Aiyub (Rev. Téc. Fac. Ing. Univ. Zulia)
The effects of Hall currents on the Rayleigh-Taylor instability of an incompressible, finitely conducting viscoelastic fluid were investigated. It is assumed that the fluid is permeated by a uniform two-dimensional horizontal magnetic field. It is shown that the solution is characterized by a variational principle. Proper solutions were obtained for a semi-infinite fluid in which the density varies exponentially in the vertical direction. The dispersion relation was derived and solved numerically. It was found that Hall currents and finite conductivity have a destabilizing influence, while viscosity and elasticity have a stabilizing influence on the growth rile of the unstable mode of disturbances.